2011
DOI: 10.1007/s00101-011-1926-8
|View full text |Cite
|
Sign up to set email alerts
|

ProSeal®-Kehlkopfmaske in normalgewichtigen und adipösen Patienten

Abstract: The application of PEEP when PCV is used with the PLMA results in improved oxygenation in obese patients with a BMI ≥30 and <36 kg/m(2) but not in normal weight patients. Alveolar recruitment produced by seal pressure measurements below 30 cm H(2)O was sufficient to produce a clinically significant improvement in oxygenation in most obese patients and there was a significant improvement of oxygenation with PEEP=5 cmH(2)O. Both findings are in contrast to findings of studies using an ETT which suggests that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Whether PEEP improves gas exchange during positive pressure ventilation with an LMA mask is also unclear. Some studies are in accordance; 32,33 for example, von Goedecke et al 34 did not find a difference in oxygenation but reported an increase in PIP and compliance with increasing levels of PEEP as we do. Others are in discordance and report a significant improvement of oxygenation.…”
Section: Discussionsupporting
confidence: 82%
“…Whether PEEP improves gas exchange during positive pressure ventilation with an LMA mask is also unclear. Some studies are in accordance; 32,33 for example, von Goedecke et al 34 did not find a difference in oxygenation but reported an increase in PIP and compliance with increasing levels of PEEP as we do. Others are in discordance and report a significant improvement of oxygenation.…”
Section: Discussionsupporting
confidence: 82%